Pour une « archéologie » comparée des chansons sur les parricides et les infanticides dans les recueils du Département Philosophie, histoire, sciences de l’homme de la BnF - Agnès Sandras (Criminocorpus)
There are specific collections (named “recueils”) on criminal complaints at the National Library of France. This article examines the why and how of these collections: who fed them, for what purpose, and by obeying what motivations. To answer these questions, soliciting professional memory is necessary and using the multiple investigative possibilities provided by the documents digitized by the library and other institutions.